First observation of the B+ → D+s⁢D-s⁢K+ decay - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; Li, Peilian; et al. (Physical review, 2023)
The 𝐵+ →𝐷+𝑠⁢𝐷−𝑠⁢𝐾+ decay is observed for the first time using proton-proton collision data collected by the LHCb detector at center-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. Its branching fraction relative to that of the 𝐵+ →𝐷+⁢𝐷−⁢𝐾+ decay is measured to be ℬ⁡(𝐵+→𝐷+𝑠⁢𝐷−𝑠⁢𝐾+)ℬ⁡(𝐵+→𝐷+⁢𝐷−⁢𝐾+) =0.525 ±0.033 ±0.027 ±0.034, where the first uncertainty is statistical, the second systematic, and the third is due to the uncertainties on the branching fractions of the 𝐷±𝑠 →𝐾∓⁢𝐾±⁢𝜋± and 𝐷± →𝐾∓⁢𝜋±⁢𝜋± decays. This measurement fills an experimental gap in the knowledge of the family of Cabibbo-favored ¯𝑏 →¯𝑐⁢𝑐⁢¯𝑠 transitions and opens the path for unique studies of spectroscopy in future.
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 1047 weitere Personen]
Im Titel sind die Plus- und Minuszeichen hochgestellt sowie "s" jeweils tiefgestellt
Veröffentlicht: 14. August 2023
Gesehen am 12.05.2025